2019
DOI: 10.1152/advan.00002.2019
|View full text |Cite
|
Sign up to set email alerts
|

Elementary school classroom physical activity breaks: student, teacher, and facilitator perspectives

Abstract: Current physical activity (PA) guidelines recommend that children accumulate at least 60 min of PA each day, and that adults should collaborate across sectors to increase opportunities for PA. Implementing brief classroom PA breaks (CPABs) is one way to help increase daily PA. The primary purpose of this study was to determine perceptions of a 14-wk CPAB program among elementary school children, in the first through fourth grades ( n = 254), at a suburban elementary school, and their teachers ( n = 18). The CP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 45 publications
1
22
0
2
Order By: Relevance
“…This happens because of habits in learning that only focus on solving mathematical problems and applying examples in textbooks. For this group, the emphasis is needed on strict instruction and guidance from the facilitator to keep directing students on the track [26,27,28]. In this group, it cannot be expected that creativity arises from solving problems.…”
Section: Resultsmentioning
confidence: 99%
“…This happens because of habits in learning that only focus on solving mathematical problems and applying examples in textbooks. For this group, the emphasis is needed on strict instruction and guidance from the facilitator to keep directing students on the track [26,27,28]. In this group, it cannot be expected that creativity arises from solving problems.…”
Section: Resultsmentioning
confidence: 99%
“…The classroom setting is considered as a good environment to implement physical activity-based interventions [ 19 , 20 , 21 , 22 ], as the children are easily reached this way and teachers have a large degree of autonomy to decide the most appropriate time to implement a physical activity break [ 23 , 24 ]. Physical activity breaks within a classroom setting are hypothesized to demonstrate effects on academic performance and cognitive outcomes according to the embodied cognitive loading theory [ 25 ] in addition to providing health-related benefits.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to potential health benefits, CPA also can have a positive impact on academic-related outcomes and students' on-task behaviour (Goh et al, 2016;Watson et al, 2017). CPA provides possibilities for children to increase energy expenditure, enhance physical competency, diversify social interactions, and ingrain habits of daily PA (Mullins et al, 2019), while studies in CPA have revealed that students enjoyed participating and became more excited about school because of the activities (Barr-Anderson et al, 2011;Gibson et al, 2008). There is some research indicating that health behaviour (i.e., PA and nutrition) can be promoted by interventions that develop personal agency (Contento et al, 2007).…”
Section: Introductionmentioning
confidence: 99%